ynthesis and Biological Activity Study of New Some Schiff Bases Derived From D-Erythroascorbic Acid - Rumez, Rasmia M; Abdul-Razaq, Alia´a S; Hassan, Dheefaf F; Hussin, Zinah H (Al-Nahrain Journal of Science, 2018)
New Schiff bases derived from D-erythroascorbic acid were prepared by condensing pentulosono-γ-lactone-2,3-enedianisoate (V) with 3-amino phenol, (4-iodo, 3-methoxy, 4-methyl, 4-nitro) aniline in the presence of glacial acetic acid and dry benzene. The products were characterized by spectral methods FTIR, and some by (UV-Vis), 1H and 13CNMR, mass spectra and measurement of its physical properties and evaluation of the biological activity for them.